Islamiat class 3 - Dr Muhammad idress (Punjab curriculum and textbook board Lahore, 2022)
Islamiat textbook designed to impart essential Islamic knowledge, teachings, and ethical values to students, helping them strengthen their faith and understanding of Islam.